Encyclopedia of Buddhist Arts: Painting - Supervised by Venerable Master Hsing Yun (Encyclopedia of Buddhist Arts, 2016)
The Encyclopedia of Buddhist Arts is the first comprehensive collection of world Buddhist Arts. The collection includes nearly 10,000 entries and over 14,000 pictures, divided into the categories of Caves and Rock Carvings, Architecture, Sculpture, Painting, Calligraphy and Seal Engraving, Artifacts and Decorative Arts, and People.